Zooplankton from Erken, 2012-01-18–2022-12-06 - Erken Laboratory (Uppsala University, 2026)
A comprehensive survey of zooplankton from grab samples collected throughout the lake water column, containing data on zooplankton abundance and species composition
Erken Laboratory (2026). Zooplankton from Erken, 2012-01-18–2022-12-06 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Y3x7uX_Hr4b7I7ngx7HmDWct
Keywords: Erken Laboratory; Biomass Dynamics; Ecosystem Function; Lake; Zooplankton; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap